Thermal Decomposition of Barium Nitrate in Presence of Certain Metal Oxides - I. Maliakkal, Babu; D. Radhakrishnan Nair, T. (Asian Journal of Chemistry, 2010)
Thermal decomposition of barium nitrate in presence of several metal oxides has been studied by thermogravimetry. Kinetic parameters are determined by the Freemann-Carroll and Horowitz-Metzger methods. The behaviour of different oxides has beenfound to be different and quite specific.